1989
DOI: 10.1227/00006123-198904000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Nerve Roots of the Cauda Equina: Clinical Aspects and Consideration of Pathogenesis

Abstract: In order to investigate the clinical significance of redundant nerve roots of the cauda equina (RNR) and their pathogenesis, the following studies were performed: 1) examination of 1,256 myelograms of patients with lumbar disease; 2) clinical analysis of 55 patients with RNR and 75 without RNR; 3) electrophysiological examination of 9 patients with RNR; and 4) anatomical and histopathological examination of 6 autopsy cases. RNR were found in 42% of patients with severely constricted spinal canals. In comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 0 publications
5
84
2
1
Order By: Relevance
“…The literature describes this entity in association with degenerative spinal canal stenosis ( Figure 1). It is believed that the acquired elongation of the nerve roots is due to a chronic compression force at the level of the lumbar spinal stenosis (LSS) 9 . This condition is not a new or separate disease but may be part of the natural evolution of lumbar canal stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature describes this entity in association with degenerative spinal canal stenosis ( Figure 1). It is believed that the acquired elongation of the nerve roots is due to a chronic compression force at the level of the lumbar spinal stenosis (LSS) 9 . This condition is not a new or separate disease but may be part of the natural evolution of lumbar canal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of RNRCE in diagnostic imaging is especially important for avoiding the misdiagnosis of other diseases, such as arteriovenous malformations 9 . The reported prevalence of RNRCE varies, with some researchers determining prevalence values of 33.8% to 42% in patients with spinal canal stenosis 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In LCS patients, myelography and MRI often reveal a redundant nerve root (RNR). Suzuki et al 42 pathologically investigated the cauda equina at autopsy and reported that the cause of nerve root redundancy was Wallerian degeneration. Takeno et al 43 administered PGE 1 on a daily basis for 2 weeks to LCS patients with NIC and reported that MRI showed RNR in 56% of the patients in whom NIC did not resolve, while enhanced MRI showed intraradicular edema in 84% of them.…”
Section: Discussionmentioning
confidence: 99%